Physician Weight-Related Counseling Is Unrelated to Extreme Weight Loss Behaviors Among Overweight and Obese Adolescents. (July 2018) - Bravender, Terrill; Lyna, Pauline; Coffman, Cynthia J.; Bodner, Michael E.; Østbye, Truls; Alexander, Stewart C.; Lin, Pao-Hwa; Pollak, Kathryn I.
Some physicians may be hesitant to counsel overweight and obese adolescents about weight because of concerns that such counseling may result in extreme weight loss behaviors and the subsequent development of eating disorders. We compared self-reported extreme weight loss behaviors in 535 overweight/obese adolescents prior to receiving weight-related counseling during primary care visits, and again after 3 months. We found no change in fasting (7.7% vs 6.3%, P = .45), and decreases in diet pill use (4.1% vs 1.7%, P = .003) and laxative use/vomiting (2.6% vs 1.0%, P = .02). Three months following their medical appointment, patients were also less likely to report trying to lose weight in general (80.0% vs 75.6%, P = .04). Physicians should be reassured that providing weight-related counseling to their obese adolescents is unlikely to induce extreme weight loss behaviors. Frequent counseling may be required in order to help patients maintain motivation to attain a healthy weight.